WAYS TO INCREASE THE EFFECTIVENESS OF REHABILITATION MEASURES IN PATIENTS UNDER SURGICAL BREAST ENDOPROSTHETICS - O.O. Ismati; E.V. Zinoviev; I.B. Mustafakulov; Z.A. Dzhuraeva; Ismati Odiljon Obidovich; Mustafakulov Ishnazar Boynazarovich; Juraeva Zilola Aramovna (Research Focus International Scientific Journal, 2023)
Breast prosthetics for aesthetic purposes is widespread throughout the world and has been rapidly spreading in Uzbekistan in recent years. As a result of surgical endoprosthetics of breast tissue with silicone implants in the early and late postoperative periods, patients’ bodies often experience typical postoperative pain, which, if subclinical, requires constant dynamic monitoring and preventive rehabilitation procedures. Rehabilitation measures are a prerequisite for a successfully performed aesthetic surgery to enlarge the mammary glands. To address the effectiveness of intramuscular botulinum toxin A and the INDIBA electromagnetic field electrophysiology we used , a prospective randomized trial was designed to evaluate the effectiveness of patient-reported postoperative pain and pain reduction in these settings.